Աբխազիայի կարգավիճակի հարցը Վրաստանի հանրապետության վարչական համակարգի մեջ (մարտ 1919 թ. – փետրվար 1921 թ.) - Մաիլյան, Բենիամին («Զանգակ - 97»)
The Constituent Assembli of Georgia gives autonomy functions to regional organs of selfgovemment - called Zemstvo. Each region of Georgia were became territorial autonomy. "Autonomy" institutions of Abkhazia - National Council and Commissariats were considcred as Zemstvo. Zemstvo's rights of Abkhazia regions were repressed by this. To even the rights of Abkhazia regions and the rest part of Georgia it was needcd to convcrt the National Council to lagislative Organ, forward the State governing to Commissariats, to free them off from the functions of Zemstvo. So Autonomy of Abkhazia would gain the political character instead of assumptive territorial one. Georgian politicians were not agree with this, which were beware of damaging the soveregnity of Georgia. Declarative character of Abkhazian autonomy arized becouse of the risk that it real autonomy is provided so it will lead to Separation of Abkhazia from Georgia.
Keywords: Պատմություն; Քաղաքականություն